US foreign policy and defense strategy the evolution of an incidental superpower - Reveron, Derek S.; Gvosdev, Nikolas K. 1969-; Owens, Mackubin Thomas 1945- (Georgetown University Press, 2015)
This work analyzes the strategic underpinnings of US defense strategy and foreign policy since 1945. Primarily intended to be a supplemental textbook, it explains how the United States became a superpower, examines the formation of the national security establishment, and explores the inter-relationship between foreign policy, defense strategy, and commercial interests. It differs from most of the existing teaching texts because its emphasis is not on narrating the history of US foreign policy or explaining the policymaking process. Instead, the emphasis is on identifying drivers and continuities in US national security interests and policy, and it has a special emphasis on developing a greater understanding of the intertwined nature of foreign and defense policies. The book will conclude by examining how the legacy of the last sixty-five years impacts future developments, the prospect for change, and what US national security policy may look like in the future